Synopsis of hip surgery - Nho, Shane J. (Thieme, 2021)
A reader-friendly overview of the fundamentals in hip pathology and treatment presented by esteemed experts! Synopsis of Hip Surgery by renowned hip specialists Shane Nho, Joshua Harris, Brett Levine, and an impressive group of contributors provides a well-rounded perspective on the surgical and nonsurgical management of common to rare hip conditions. The generously illustrated clinical reference is both concise and comprehensive, not only encompassing the full age continuum but also a wide array of hip disorders such as congenital and degenerative issues and problems associated with sports